HUBUNGAN MOTIVASI BELAJAR DENGAN KEMATANGAN KARIR SISWA XI TEKNIK AUDIO VIDIO SMK NEGERI 2 SALATIGA - Elsanidia Della; Tritjahjo Danny Soesilo; Yustinus Windrawanto (Indonesian Journal Of Educational Research and Review, 2018)
This study aims to determine the significance of the relationship between learning motivation and career maturity in the students of Class XI Audio Vidio (TAV) in Salatiga Vocational High School number  2 . This type of research is a correlation consisting of two variables: learning motivation and career maturity. The subjects of this study were students of class XI TAV (A and B) totaling 66 people through total sampling technique. Data collection for both variables using a questionnaire. Analysis using Kendall Tau technique. From the results of data analysis, the correlation coefficient (r) between the variables of learning motivation and student career maturity was obtained at r = 0.735 and p value 0.000. Shows that learning motivation contributes positively and significantly to students' career maturity. A positive and significant relationship between learning motivation and career maturity in class XI students of Salatiga Vocational High School number  2. The conclusion of this study is that the higher the learning motivation, the higher the student's career maturity, and vice versa.Keywords: Learning Motivation, Career Maturity